Ice friction of flared ice hockey skate blades - Federolf, P. A.; Mills, R.; Nigg, B. (Journal of Sports Sciences, 2008)
In ice hockey, skating performance depends on the skill and physical conditioning of the players and on the characteristics of their equipment. CT Edge have recently designed a new skate blade that angles outward near the bottom of the blade. The objective of this study was to compare the frictional characteristics of three CT Edge blades (with blade angles of 4°, 6°, and 8°, respectively) with the frictional characteristics of a standard skate blade. The friction coefficients of the blades were determined by measuring the deceleration of an aluminium test sled equipped with three test blades. The measurements were conducted with an initial sled speed of 1.8 m · s-1 and with a load of 53 kg on each blade. The friction coefficient of the standard blades was 0.0071 (s=0.0005). For the CT Edge blades with blade angles of 4°, 6°, and 8°, friction coefficients were lower by about 13%, 21%, and 22%, respectively. Furthermore, the friction coefficients decreased with increasing load. The results of this study show that widely accepted paradigms such as "thinner blades cause less friction" need to be revisited. New blade designs might also be able to reduce friction in speed skating, figure skating, bobsledding, and luge.